Starting university during the pandemic: First-year international students’ complex transitions under online and hybrid-learning conditions - Wang, Lizhou (Frontiers in Psychology, 2023)
International education activities suddenly halted due to the COVID-19 pandemic, severely disrupting student mobility and academic learning. Many educational institutions have delivered programs to students through digital devices globally rather than in situ. Such a shift presents a unique opportunity to assess the impact of online and hybrid education for international students. This qualitative study interviewed 30 international students who had arrived on campus and shared their first-year university transition experiences during the pandemic. The analysis shows that spatial and temporal circumstances created two scenarios and thus resulted in different first-year university experiences. Although all students were dissatisfied with online learning, studying at a distance in different time zones was particularly detrimental to international students’ mental and physical health. The (im)mobile environments led to mismatches in expectations, roles, activities, and realities, negatively affecting student learning and adjustment. This study highlights the complex international transition issues and offers implications for sustainable online and hybrid learning practices in the educational system.